Phylogenetic systematics, ecology, and conservation of marsupial frogs (Anura: Hemiphractidae) from the Andes of southern Ecuador, with descriptions of four new biphasic species - Carvajal-Endara, Sofía; Coloma, Luis A.; Morales-Mite, Manuel A.; Guayasamin, Juan M.; Székely, Paul; Duellman, William E. (Zootaxa, 2019)
We review the systematics of the species of Gastrotheca (Anura: Hemiphractidae) in the highlands of the southern Ecuadorian Andes. We analyzed phylogenetic, morphological, ecological, and acoustic data from populations in the region. We provide an updated phylogenetic hypothesis inferred from a database that contains 42 species of Gastrotheca, and sequences from mitochondrial (12S, 16S, and ND1) and nuclear (POMC and RAG-1) genes. We describe four new endemic biphasic species for Ecuador (Gastrotheca cuencana, G. elicioi, G. turnerorum, and G. yacuri). In addition, we redefine G. lojana, recently resurrected from the synonymy of G. monticola, and redescribe G. litonedis. Furthermore, we describe the tadpoles and ontogenetic color changes in six species (G. cuencana, G. elicioi, G. litonedis, G. lojana, G. pseustes, and G. turnerorum). Also, we describe the calls of seven species (G. cuencana, G. elicioi, G. litonedis, G. lojana, G. pseustes, G. testudinea, and G. yacuri). The phylogenetic relationships estimated here are congruent with previous phylogenetic hypotheses for the group, except for the placement of G. galeata, G. plumbea, G. orophylax, G. nicefori, and G. griswoldi. Because most sister species in Gastrotheca are allopatric, the evolutionarly scenarios that likely have intervened in shaping the diversity are the uplift of the Andes and the formation of cross-Andean river valleys, which probably promoted conditions that acted as dispersal barriers that led to speciation. Many species of Gastrotheca (44%) are highly threatened. Most monophasic species have not been seen since the late 1980s, whereas the highland biphasic species have survived the catastrophic events that led to the disappearance of many other sympatric anurans. Research and conservation actions are urgently needed for all surviving species treated herein, five of which are either Critically Endangered or Endangered because of their restricted distributions (10–1600 km2), habitat destruction and fragmentation, climate change, and pathogens. Two of the new species, G. cuencana, and G. elicioi, mostly are known from the cities of Cuenca and Loja, respectively, where urbanization threatens their survival. In order to call attention to conservation issues, we name one new species to refer to the Yacuri National Park, and the other three in honor of the people from Cuenca, the Turner family, and Elicio E. Tapia, whose actions are helping to halt amphibian extinctions.